The epithelial barrier: a Janus-faced regulator in allergic airway diseases from defense to inflammation - Bao, Youwei; Chen, Qi; Shi, Binbin; Zhu, Xinhua (Frontiers in Allergy, 2025)
BackgroundThe epithelial barrier serves as the body's first line of defense between the host immune system and the external environment. Evidence confirms that epithelial barrier damage is an initial event in the pathogenesis of allergic respiratory diseases, during which the barrier exhibits a dual “Janus-faced” role.MethodsThis review synthesizes current literature to explore the molecular and cellular mechanisms underlying epithelial barrier dysfunction, including dysregulation of tight junctions, aberrant immune signaling, and release of pro-inflammatory alarmins. We also evaluate contemporary diagnostic technologies for assessing the epithelial barrier and analyze current therapeutic strategies aimed at its restoration.ResultsAn intact respiratory epithelial barrier effectively defends against allergens and pathogens. When compromised, it exacerbates inflammatory responses through the release of alarmins. Advances in omics-based profiling and advanced imaging now enable precise assessment of barrier integrity. Therapeutically, innovative strategies—including immunomodulators, biologics, and novel agents targeting epithelial repair pathways—offer promising avenues for restoring barrier function and controlling inflammation.ConclusionReal-time and effective diagnosis of epithelial barrier integrity, coupled with therapeutic strategies targeting the barrier, are pivotal for achieving long-term disease control in asthma, allergic rhinitis, and related conditions. Future research should focus on barrier-centric integrated approaches to bridge fundamental scientific discoveries with clinical applications.